Gravitationally lensed quasars in Gaia – IV. 150 new lenses, quasar pairs, and projected quasars. Issue 3 (20th December 2022) - Lemon, C; Anguita, T; Auger-Williams, M W; Courbin, F; Galan, A; McMahon, R; Neira, F; Oguri, M; Schechter, P; Shajib, A; Treu, T; Agnello, A; et al.
ABSTRACT: We report the spectroscopic follow-up of 175 lensed quasar candidates selected using Gaia Data Release 2 observations following Paper III of this series. Systems include 86 confirmed lensed quasars and a further 17 likely lensed quasars based on imaging and/or similar spectra. We also confirm 11 projected quasar pairs and 11 physical quasar pairs, while 25 systems are left as unclassified quasar pairs – pairs of quasars at the same redshift, which could be either distinct quasars or potential lensed quasars. Especially interesting objects include eight quadruply imaged quasars of which two have BAL sources, an apparent triple, and a doubly lensed LoBaL quasar. The source redshifts and image separations of these new lenses range between 0.65–3.59 and 0.78–6.23 arcsec, respectively. We compare the known population of lensed quasars to an updated mock catalogue at image separations between 1 and 4 arcsec, showing a very good match at z < 1.5. At z > 1.5, only 47 per cent of the predicted number are known, with 56 per cent of these missing lenses at image separations below 1.5 arcsec. The missing higher redshift, small-separation systems will have fainter lensing galaxies, and are partially explained by the unclassified quasar pairs and likely lenses presented in this work, which require deeper imaging. Of the 11 new reported projected quasar pairs, 5 have impact parameters below 10 kpc, almost tripling the number of such systems, which can probe the innermost regions of quasar host galaxies through absorption studies. We also report four new lensed galaxies discovered through our searches, with source redshifts ranging from 0.62 to 2.79.